Design and Fabrication of Portable Tilting Furnace for Aluminium Melting - Yusuf, Muhammad; Bahri, Syamsul; Agustinawati, Agustinawati (International Journal of Engineering, Science and Information Technology, 2022)
Machining is a metal cutting process using a machine tool. The machining process will produce the products and the chips or the scraps. The metal of machining chips made from machining processes can be recycled into new materials. The metal of machining chips can be recycled through the smelting process. This research aims to design and fabrication a crucible furnace that can support the recycling process of the metal scraps of machining chips into a new materialâ€”the stove is designed to melt non-ferrous metals using gas fuel. The tilting-pot crucible furnace type was created in this research. The crucible furnaces are used for nonferrous metals such as bronze, brass, zinc, and aluminum alloys. The crucible furnace capacities are limited to 10 kg. Liquefied Petroleum Gas (LPG) was used as the fuel for the furnace. The construction of the stove is cylindrically designed. The burner was installed upright at the bottom of the stove. The combustion process is done by mixing fuel LPG gas and air from the blower. The stove was tested on the aluminum machining chips using locally available materials in Lhokseumawe Aceh. The thermometer Lutron TM-906A was used to measure the temperature inside the crucible. From the results of the design and testing of the furnace that has been done, it can be concluded that the aluminum machining chips of 6kg are melting at a temperature of 640oC for 52 minutes, and the LPG gas fuel required is 1.30kg. The crucible furnace was designed to attain a maximum temperature of 700Â°C.